Why Do Within Firm-Product Export Prices Differ across Markets? - Holger Görg; László Halpern; Balász Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2010)
In this paper we analyse the relationship between gravity variables and f.o.b. export unit values using Hungarian firm-product-destination data. By taking firm-product level selection into account we show that export unit values increase with distance even for particular firm-product combinations. This cannot be explained by models assuming firm- or even firm-product level selection and constant markups. The differences are important quantitatively; price differences in Hungarian exports between Germany and the US are about 30%. We also show that unit values are positively related to GDP/capita and that there is a weak negative relationship between unit values and market size. We propose two possible explanations: first, firms may export different quality versions of the same product to different markets. Secondly, directly exporting firms may capture part of the markups on transport costs in their f.o.b. prices.
Keywords: D40; F12; 330; export; price; selection; Hungary; Außenhandelspreis; Preisdifferenzierung; Firmeninterner Handel; Gravitationsmodell; Transportkosten; Produktqualität; Ungarn